2010
DOI: 10.1108/13522751011078818
|View full text |Cite
|
Sign up to set email alerts
|

Examining the use of nutrition labelling with photoelicitation

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 101 publications
2
35
1
1
Order By: Relevance
“…Feunekes et al 13 examined comprehension of single label types and found that the time taken to make an evaluation increases with the complexity of the FOP label. Other studies have also shown that time taken is one factor influencing label use 5 , 8 …”
Section: Discussionmentioning
confidence: 99%
“…Feunekes et al 13 examined comprehension of single label types and found that the time taken to make an evaluation increases with the complexity of the FOP label. Other studies have also shown that time taken is one factor influencing label use 5 , 8 …”
Section: Discussionmentioning
confidence: 99%
“…Il s'agit de l'étude LABEL [23], qui a mis en évidence une influence favorable des logos (7 logos différents étaient testés, y compris l'affichage des pourcentage RNJ) sur la qualité nutritionnelle de paniers alimentaires constitués par des participants, ces derniers étant soumis à des incitations financières afin de révéler leurs vrais choix (selon les fondements de l'économie expérimen-tale). D'autres études, s'appuyant sur la photo-élicitation (prise de photos de sujets en situation d'achat en magasin et de consommation à domicile suivi d'échanges avec les mêmes sujets autour de ces photos) [24] ou sur le eyetracking (examen objectif de la façon dont sont lues les étiquettes à travers l'enregistrement des mouvements oculaires) [25] concluent qu'un logo face-avant peut aider les consommateurs à faire plus rapidement des choix plus sains.…”
Section: Discussionunclassified
“…In this regard, Polit, Beck and Hungler (2001) recommend that not more than ten interviewees should be included in the study, to allow an in-depth exploration of topics in phenomenological studies. Furthermore, the sample of six respondents is considered suitable since a similar sample has been used in comparable studies (Tijani, Fifield and Power, 2009;Koenigstorfer and Klein, 2010). It is worth noting that all the interviews were reviewed several times before been transcribed.…”
Section: Methodsmentioning
confidence: 99%